IDEOLOGICAL BIASES IN TRANSLATING THE QUR’AN: AN ANALYSIS STUDY OF AL-QUR’AN TARJAMAH TAFSIRIYAH BY MUHAMMAD THALIB - Amulisi, Sibro (Universitas Nurul Jadid, 2023)
This paper examines the translation of the Qur’an in Indonesia, which is a sign of the interaction of Muslims in Indonesia with the Holy Scriptures, which is not limited to reading and studying it in the original Arabic pronunciation. Like the interpretation of the Qur’an, which is full of dynamics, the translation also touches on the realm of polemics that attract the attention of adherents from different circles. The polemic in question can be found among the long historical translation buildings. In this study, the author chooses Al-Qur’an Tarjamah Tafsiriyah by Muhammad Thalib, in which the ideological bias of his organizational group is indicated. Is there an ideological bias produced by Muhammad Thalib in his translation work? This study attempts to answer the above questions using a qualitative method based on library research, with a social identity approach and critical discourse analysis as its formal object. In addition, this study will use the hermeneutical analysis offered by Sahiron Syamsudin. In addition, the method used in this qualitative research is content analysis to analyze the results of Muhammad Thalib's translation, leading to a narrative justification of his ideology. Finally, this research resulted in a conclusion that the results of Muhammad Thalib’s translation of the Qur’an in the form of Al-Qur’an Tarjamah Tafsiriyah in it are indeed many translations that have an interest in defending his organizational group, MMI (Majelis Mujahidin Indonesia), which adheres to the ideological ideology of Islamism which departs from the view of integral Islam and is an incarnation of the reproduction of Islamic Revivalism and Neo-revivalism which tends to be traditional and conservative as found in the Wahhabiyah, Ikhanul Muslimin, and Jemaah Islamiyyah movements in the Thaliban